2006
DOI: 10.1653/0015-4040(2006)89[63:gvwabs]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation Within and Between Strains of the Fall Armyworm, Spodoptera Frugiperda (Lepidoptera: Noctuidae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 31 publications
3
27
0
3
Order By: Relevance
“…This insect preference and best performance for grasses has been previously demonstrated by other researchers. S. frugiperda preferred grasses such as maize, sorghum, and bermudagrass, which are C 4 plants, as opposed to C 3 plants such as cotton or soybean (Buntin, 1986;Lewter et al, 2006;Nagoshi et al, 2007). This might be due to the composition and nutritional adequacy of these plants in relation to hosts from other botanical families (Pashley, 1986(Pashley, , 1988Barros et al, 2010) with the consequence that, ultimately, insect foraging is an exercise in acquiring the best blend and balance of suite nutrients, including amino acids, carbohydrates, sterols, phospholipids, fatty acids, vitamins, minerals, trace elements, and water (Behmer, 2009 , and inorganic phosphate from 20 to 60 50 mg dm −2 (Mondal et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…This insect preference and best performance for grasses has been previously demonstrated by other researchers. S. frugiperda preferred grasses such as maize, sorghum, and bermudagrass, which are C 4 plants, as opposed to C 3 plants such as cotton or soybean (Buntin, 1986;Lewter et al, 2006;Nagoshi et al, 2007). This might be due to the composition and nutritional adequacy of these plants in relation to hosts from other botanical families (Pashley, 1986(Pashley, , 1988Barros et al, 2010) with the consequence that, ultimately, insect foraging is an exercise in acquiring the best blend and balance of suite nutrients, including amino acids, carbohydrates, sterols, phospholipids, fatty acids, vitamins, minerals, trace elements, and water (Behmer, 2009 , and inorganic phosphate from 20 to 60 50 mg dm −2 (Mondal et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Sosa-Gómez (2004) also found high gene flow in Biochem Genet (2011) 49:760-787 761 A. gemmatalis, using random amplification of polymorphic DNA. Lewter et al (2006) evaluated the genetic structure of the migratory fall armyworm, S. frugiperda (J. E. Smith), across part of its range in America using mitochondrial COI and COII and the nuclear internal transcribed spacer 1 (ITS1) of ribosomal RNA; it was demonstrated that all individuals could be divided into three corn and four rice strain haplotypes. The range of genetic divergence between the two strains was 0.66-0.99% on the basis of the COI and COII genes, but no variation was detected by ITS1.…”
Section: Introductionmentioning
confidence: 99%
“…Estos resultados demuestran que los haplotipos de maíz y arroz de este país, se mueven dentro de cada uno de estos cultivos y por lo tanto muestran una asociación a su planta hospedera respectiva. Este mismo resultado fue obtenido por Lewter et al (2006) en un trabajo en el que analizaron 71 secuencias de S. frugiperda de Estados Unidos y en el que encontraron tres haplotipos exclusivos del cultivo de maíz y cuatro haplotipos exclusivos del cultivo de arroz. Los haplotipos identificados por estos últimos autores fueron utilizados en el presente trabajo para compararlos con los haplotipos de la misma especie en Colombia.…”
Section: Discussionunclassified